Pemanfaatan Belimbing Wuluh Sebagai Alternatif Larutan Deparafinisasi Mikro Pada Jaringan Mammae - Fransiska Ayuningtyas Widyastani; Nadilla Apriliyani Widyaningtyas; Adjeg Tarius (Jurnal Nurse, 2021)
The deparaffinization stage in HE staining usually using xylol, but xylol has a toxic, volatile and flammable effect. An alternative solvent that can be used as a substitute for xylol is Averrhoa bilimbi solution which contains citric acid and has characterized that are easy to obtain, derived from nature and safe to use. This study aims to determine whether there are differences in the microscopic image (shape, color and cell background) of mammary tissue micro-deparaffinized with xylol and Averrhoa bilimbi solution. This type of research is an experimental study using mammae tissue samples with saturated samples using 2 variations of micro deparaffinization treatment, namely deparaffinization with Averrhoa bilimbi solution and deparaffinization using xylol. The results obtained were carried out by descriptive test, then the normality test using two pairs of data with the results on the shape, color and background are not normal, namely 0.000. The Wilcoxon test was carried out further with the results of cell shape, cell color and background p <0.05, which indicated that the shape, color and background of the two treatments had significant difference.